PENGUKURAN KINERJA PORTOFOLIO SAHAM MENGGUNAKAN MODEL BLACK-LITTERMAN BERDASARKAN INDEKS TREYNOR, INDEKS SHARPE, DAN INDEKS JENSEN (Studi Kasus Saham-Saham yang Termasuk dalam Jakarta Islamic Index Periode 2009-2013) - Siti Azizah; Sugito Sugito; Alan Prahutama (Jurnal Gaussian, 2014)
The composing of portfolio is one of the way to minimize the risk of investment. Through portfolio, it is expected that some stocks still give return when other stocks are loss. From this composed portfolio, every investor expect appropriate return. The higher the return is better. Black-Litterman Model is the method which optimize the investor’s return by giving difference financial capital proportion for every stocks of portfolio. This method combines both the aspect historical data and the investor view to make new prediction about return of portfolio as the basic to compose the weight model of assets. Investor often compose some portfolio to plan their investment, to compare the performance (capability to produce return and also risk) from any number of portfolio, before evaluating whether the performance of chosen portfolio has been appropriate with the expectation. The measurement of the performance of portfolio is done by using Sharpe, Treynor, and Jensen Indeks. The result of the case study of eleven Jakarta Islamic Indexstocks in the period of 2009-2013 recommend the portfolio with the best perform, whichis optimized which Black-Litterman Model. Based on Sharpe Indeks, the best portfolio consists of SMGR 60,79% and INTP 39,21% of capital allocation. Based on Treynor and Jensen Indeks, the best portfolio consists of SMGR 22,59%, INTP 37,67%, PTBA 1,62%, ANTM 2,69%, ITMG 16,17%, and KLBF 19,26%. Keywords :     JII, Portfolio, Black-Litterman Model, Treynor Index, Sharpe Index, Jensen Index.